DOI: 10.1007/978-3-540-85209-4_15
|View full text |Cite
|
Sign up to set email alerts
|

Adapting BitTorrent to Wireless Ad Hoc Networks

Abstract: Abstract. BitTorrent is one of the Internet's most efficient content distribution protocols. It is known to perform very well over the wired Internet where end-to-end performance is almost guaranteed. However, in wireless ad hoc networks, many constraints appear as the scarcity of resources and their shared nature, which make running BitTorrent with its default configuration not lead to best performances. To these constraints it adds the fact that peers are both routers and end-users and that TCP-performance d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
9

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 11 publications
1
16
0
9
Order By: Relevance
“…Through new peer neighbor selection and content pieces selection strategies, our solution is topology-aware and ensures fair sharing. These strategies have been described in details in our research work [2]. Globally, we found that the best to do is to share the most data with physical neighbors to reduce the network overhead and to realize the maximum throughput, while sending pieces of content from time to time to far peers to provide them with material to share and keep them busy.…”
Section: Requirements Analysismentioning
confidence: 94%
See 3 more Smart Citations
“…Through new peer neighbor selection and content pieces selection strategies, our solution is topology-aware and ensures fair sharing. These strategies have been described in details in our research work [2]. Globally, we found that the best to do is to share the most data with physical neighbors to reduce the network overhead and to realize the maximum throughput, while sending pieces of content from time to time to far peers to provide them with material to share and keep them busy.…”
Section: Requirements Analysismentioning
confidence: 94%
“…plugged and used into mobile devices [2]. Indeed, on one hand, their algorithms are not adapted to the constraints of multi-hop wireless networks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is contradictory to the goals of BitTorrent and is not suitable for wireless ad hoc networks. In another previous work [3], we propose replicating the initial seed of the content at the edge of the network in order to increase the diversity and improve the parallelism. Although these policies recofd better download times and point to some new directions, they are limited to some specific cases that need to be generalized to clearly illustrate the relationship between content replication, user performance, fairness and overhead on the underlying network.…”
Section: Introductionmentioning
confidence: 99%